2020
DOI: 10.1111/bph.15224
|View full text |Cite
|
Sign up to set email alerts
|

Sigma 1 receptor as a therapeutic target for amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is an adult disease causing a progressive loss of upper and lower motoneurons, muscle paralysis and early death. ALS has a poor prognosis of 3–5 years after diagnosis with no effective cure. The aetiopathogenic mechanisms involved include glutamate excitotoxicity, oxidative stress, protein misfolding, mitochondrial alterations, disrupted axonal transport and inflammation. Sigma non‐opioid intracellular receptor 1 (sigma 1 receptor) is a protein expressed in motoneurons, main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 150 publications
0
27
0
Order By: Relevance
“…We demonstrated that ALS-causing E102Q variant acts as a lossof-function mutant that disrupts S1R targeting to MAMs (Fig 1A). S1R is considered to be a potential drug target for treatment of neurodegenerative disorders and cancer (Herrando-Grabulosa et al, 2020;Kim & Maher, 2017;Maurice & Goguadze, 2017;Maurice & Su, 2009;Nguyen et al, 2017;D. A. Ryskamp et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that ALS-causing E102Q variant acts as a lossof-function mutant that disrupts S1R targeting to MAMs (Fig 1A). S1R is considered to be a potential drug target for treatment of neurodegenerative disorders and cancer (Herrando-Grabulosa et al, 2020;Kim & Maher, 2017;Maurice & Goguadze, 2017;Maurice & Su, 2009;Nguyen et al, 2017;D. A. Ryskamp et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A. Ryskamp et al, 2019). S1R agonists demonstrated neuroprotective effects in a variety of neurodegenerative disease models and are currently in clinical trials for a variety of neurological disorders including AD, HD, ALS, PD (Brimson, Brimson, Chomchoei, & Tencomnao, 2020;Herrando-Grabulosa et al, 2020;Maurice & Goguadze, 2017;Reilmann et al, 2019;D. A. Ryskamp et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALS is a multifactorial disease characterized by cerebral cell dysfunction and mitochondrial alteration. It is associated with the progressive increase in neuroinflammation, generalized oxidative stress, and metabolic alterations [186,187]. Saeed et al [188] identified high linkage disequilibrium in PON2 and PON3 genes.…”
Section: Pon2 and Neurodegenerationmentioning
confidence: 99%
“…They act as chaperone proteins and modulate essential processes for motor neuron survival, so that targeting these receptors may be a useful way to reduce the death of these neurons. This is extensively addressed in the review by Xavier Navarro and coworkers, which seeks to validate the neuroprotective properties of different ligands for these receptors (Herrando‐Grabulosa, Gaja‐Capdevila, Vela, & Navarro, 2020).…”
Section: Figurementioning
confidence: 99%